2019
DOI: 10.1111/ijn.12771
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐life nursing care practice in long‐term care settings for older adults: A qualitative systematic review

Abstract: Aim To synthesize qualitative evidence on nurses' end‐of‐life care practices in long‐term care settings for older adults. Background Qualitative evidence on how nurses describe their own end‐of‐life care practice has not been reviewed systematically. Design Qualitative systematic review. Data Sources Databases MEDLINE, CINAHL, PsycINFO, EMBASE, Mednar, Google Scholar, and Ichushi were searched for published and unpublished studies in English or Japanese. Methods The review followed the Joanna Briggs Institute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
(134 reference statements)
0
17
0
Order By: Relevance
“…The remaining type was a fee-based home for the elders (FHE)-a private facility that receives LTC insurance benefits for providing EOL care. These facilities differ with regard to accommodation criteria, medical services offered, and staffing (Ministry of Health, Labour, & Welfare, 2016). Nursing roles in each facility somewhat differ in responsibilities for implementing medical care, but it is common to give daily care for residents in collaboration with other healthcare professionals in such facilities.…”
Section: Sample/participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining type was a fee-based home for the elders (FHE)-a private facility that receives LTC insurance benefits for providing EOL care. These facilities differ with regard to accommodation criteria, medical services offered, and staffing (Ministry of Health, Labour, & Welfare, 2016). Nursing roles in each facility somewhat differ in responsibilities for implementing medical care, but it is common to give daily care for residents in collaboration with other healthcare professionals in such facilities.…”
Section: Sample/participantsmentioning
confidence: 99%
“…A cross-national comparison of death location (Broad et al, 2013) showed that a median of 18% older people died in LTC settings, with percentages doubling with each 10-year increase in age, indicating the need to optimize models of EOL care in these settings. In Japan, 10% of people die in LTC settings (Ministry of Health, Labour, & Welfare, 2019) and the number of older adults dying in the country's LTC settings is expected to increase markedly in the coming years because of the large older adult population (Ikegami & Ikezaki, 2013). While a systematic review (Nasu, Konno, & Fukahori, 2019) has described nurses' roles in providing EOL care in LTC settings, research has only provided short-term and partial explanations of nurses' involvement in residents' dying processes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations